Waqf Literacy of Generation Z in Indonesia - Rodame Monitorir Napitupulu; Hasnan Habib Harahap; Anny May Saroh Simamora (Universitas Pendidikan Indonesia, 2021)
AbstractPurpose - Indonesian people are recorded to have a low waqf literacy index still. In 32 provinces surveyed by the central National Zakat Agency (BAZNAS) and the Indonesian Waqf Board (BWI), only 13 provinces had moderate waqf literacy indexes, and the rest were in a low category. Meanwhile, there is no data related to the waqf literacy index in generation Z. This study aims to determine the waqf literacy index in generation Z case study at students in Faculty of Islamic Economics and Business IAIN Padangsidimpuan.Methodology - The number of samples in this study was 313 respondents. The Waqf Literacy Index is assessed in 2 dimensions: basic knowledge of Waqf and advanced knowledge of Waqf. Data is processed and analyzed by the weighted-average method in which all indicators are considered equally important.Findings - Based on the results of data analysis, it is known that the basic knowledge of the waqf score is very high, while the advanced knowledge of the waqf score is high. Waqf index literacy of generation Z in Indonesia was 83.48.Keywords - Literacy, Waqf, Understanding